Occurrence, spatiotemporal variation, and ecological risk of antibiotics in the water of the semi-enclosed urbanized Jiaozhou Bay in eastern China. (1st October 2020) - Lu, Shuang; Lin, Chunye; Lei, Kai; Wang, Baodong; Xin, Ming; Gu, Xiang; Cao, Yuanxin; Liu, Xitao; Ouyang, Wei; He, Mengchang
Highlights: The urbanized bay was heavily contaminated by amoxicillin and fluoroquinolones. Total antibiotic concentrations were 71.8~840 ng L −1 for the estuarine water and 38.7~181 ng L −1 for the bay water. Total antibiotic concentrations in the bay water were significantly higher in winter than in summer. Spatiotemporal changes in antibiotics were driven by their sources and runoff dilution. Amoxicillin and enrofloxacin presented high risks to algae in the urbanized bay. Abstract: The occurrence, temporal variation, and spatial variation of antibiotics in coastal bays and estuaries worldwide are not well documented or understood. Fifteen target antibiotics within the five classes of β-lactams, amphenicols, macrolides, fluoroquinolones, and sulfonamides were measured during the summer and winter in the water of Jiaozhou Bay in China, which is a semi-enclosed urbanized bay. Fourteen antibiotics (excluding tylosin) were detected, thus demonstrating the widespread occurrence of their residues in the bay. The total antibiotic concentration ranged from 71.8 ng L −1 to 840 ng L −1 for the estuarine water, which was significantly higher than that for the bay water (38.7–181 ng L −1 ). The antibiotic classes in the bay water were dominated by fluoroquinolones and β-lactams, which accounted for nearly 90% of the total antibiotic concentration. In addition, amoxicillin contamination was the most prominent among the 14 detected antibiotics as it accounted for ~44% of the total antibiotic concentration. The concentrations of amoxicillin, leucomycin, enrofloxacin, and sulfamonomethoxine in the bay water were usually higher than those reported for coastal bays and estuaries worldwide. The average total antibiotic concentration in the bay water was 84.7 ng L −1 during the summer, which was significantly lower than that during the winter (129.0 ng L −1 ). This was mainly due to high dilution by runoff during the summer. The florfenicol concentration in the bay water was significantly higher during the summer than in winter due to its higher usage in aquaculture during the summer. Spatially, the total antibiotic concentration (both summer and winter) was higher in the water along the eastern coast of the bay, where the population and hospital densities are high. However, the sum of the veterinary antibiotic concentrations was higher in the northeastern aquaculture area of the bay during the summer. A risk assessment revealed that amoxicillin and enrofloxacin could pose high risks (risk quotient of > 1) to algae in the bay. The synergic effects of pharmaceutical mixtures and the bioaccumulation of antibiotics through the food web should be considered in future studies. Graphical abstract: Image, graphical abstract